Relações com o saber e o universo explicativo da pessoa com cegueira total sobre a aprendizagem da geometria - Aragão, Ildema Gomes (2016)
This dissertation presents a qualitative study, whose main research question, analyze how it develops the explanatory universe of two people with total blindness on learning of geometry, from the relations with the knowledge that these individuals established to build knowledge geometric during their school lives. The research is inserted in the line of research: Science, scientific knowledge and techniques in contemporary societies of the Master in Science and Mathematics Teaching, Federal University of Sergipe. Falls into the area of Special Education and Mathematics Education in inclusive perspective. The route chosen in this work was determined by the voices of the two participants, so that through the speech, feelings and actions could explain how to build explanatory universe, which senses and relations with the knowledge established with the mathematical knowledge of geometry. The theoretical references pervade the ways of Inclusive Education (MANTOAN (2006), MANSINI (1994), SASSAKI (1999), SOUZA E SILVA (2005), SOUZA et al. (2005), STAINBACK & STAINBACK (1999), among others; and the relationship of theory and knowledge (CHARLOT 1999, 2000 , 2001 , 2005 and 2009), among others. As data collection instrument was used text production based on technical "balance of knowledge" - developed by the team ESCOL (Paris VIII), organized by Charlot (1999) - and three interview stages, one of which is based on interview technique developed by Pierre explicitness Vermersh (1994). This study was a qualitative approach involving the analysis of the content of the interviews to establish possible situations of similarities or differences between subject’s research participants. The results showed us that the person with total blindness, that does not have the involvement of other organs than sight, has the capacity to build an explanatory universe, with constructions of thought and objects of any geometric mathematical object, provided it has been prepared considering its features. The Relations with the knowledge of these people were based on the need for self-affirmation, considering them able to become independent subjects and citizens of the world.